What Can the Afghanistan Ulama Learn from The Islamic Modernism Movement in Indonesia? - Habiburrahman Rizapoor; Ghulam Mustafa Nukhba (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2021)
This article aimed to explain what the Afghan Ulama learned from the Islamic modernism movements in Indonesia in implementing the Islamic modernism values in Afghanistan. This study explored the challenges, methods of implementation of Islamic modernism values in Indonesia. This research used the analytical and descriptive method by referring to books and journal articles. This study argued that implementing Islamic modernism values in Afghanistan was a challenging and problematic process. Therefore, the Islamic Modernism movements of Afghanistan needed to work cautiously to remove obstacles and challenges calmly and without violence to pave the way for the spread of their massages. This research concluded that Islamic scholars and academics in Indonesia were mostly successful at spreading Islamic modernism values and overcoming the challenges faced with in the country. Similarly, because of the social, political and religious features; being of Indonesia as the largest Islamic country with racial and religious diversity, having the experience of Islamic modernism, and the existence of similarities between the two countries, Indonesia was an outstanding model for Afghanistan’s Islamic modernism movements. Therefore, the Afghan Islamic modernism movements can use the approaches that Indonesian Islamic modernism movements used for the spread of Islamic modernism values in the country.